Pulmonary abscess: a 111-case series in Madagascar - Rakotoson, J L; Rebasy, L; Andrianasolo, R; Rakotoharivelo, H; Rakotomizao, J R; Andrianarisoa, A C F (Médecine tropicale, 2011)
The purpose of this report is to present a series of 111 cases of pulmonary abscess observed over a 4-year period in Madagascar. There were 75 men (67.6%) and 36 women (32.4%) with a mean age of 38 years. Alcohol and tobacco use was found in 32.2% of cases. Thirteen patients (11.7%) used chewing tobacco and all patients were exposed to passive smoking. Eighty-eight patients (79.2%) had a history of bronchopulmonary disorders. Onset was progressive in 63% of cases. The main symptoms were fever (81.9%), pulmonary condensation (74.7%) and pleurisy (9.9%). Coughing was productive in 91.8% cases including 54% of patients having muco-purulent expectorations. In 49 patients (44.1%), chest radiography showed an opacity with a hydroaeric level. The abscess was solitary in 40 cases, multiple in 9, and bilateral in 5. In-hospital antibiotherapy was performed on a presumptive basis: tritherapy in 92 patients (82.9%), bitherapy in 18 (16.2%) and monotherapy in one (0.9%). Other treatment modalities inculuded respiratory kinesitherapy in 57 cases (51.3%), surgical drainage in four (3.6%) and pneumonectomy in one (0.9%). Outcome was favorable in 93 cases (8,7%) but there were 18 deaths (16.2%). This study emphasizes the value of achieving early diagnosis, identifying supporting factors and starting appropriate treatment promptly.